Boosting Project Success: Work Ethics, Climate, And Engagement as Key Drivers of Performance (Architecture Image Studies, 2025)
This study investigates how work ethics, work climate, and work engagement affect project performance in project-based organizations across Malaysia. Emphasizing Islamic work ethics in a Muslim-majority context, the research collected 310 responses from employees in five Malaysian states. Using regression and moderation analysis, the study found that both work ethics and work climate significantly enhance project performance, with work engagement serving as a key moderating factor. These findings highlight the value of cultivating ethical behavior and a supportive work environment to boost organizational success. Practical implications suggest that project managers should foster a positive climate and align ethical values with organizational goals to improve employee engagement and project outcomes. The study’s originality lies in its focus on Islamic work ethics within the Malaysian setting, offering culturally relevant insights for leaders in similar environments. By integrating ethical principles into workplace practices, organizations can drive better performance and employee commitment. This research contributes to the growing body of knowledge on project management and organizational behavior, particularly in culturally specific contexts. Future studies are encouraged to explore these dynamics across different industries and countries to broaden the applicability of the findings and deepen understanding of how ethical and environmental factors shape project success globally.